Impact of fast and slow pyrolysis on the degradation of mixed plastic waste: Product yield analysis and their characterization. Issue 6 (December 2019) - Singh, Rohit Kumar; Ruj, Biswajit; Sadhukhan, A.K.; Gupta, P.
Abstract: This work primarily investigated the pyrolysis of post-consumer mixed plastic wastes during slow pyrolysis (non-isothermal) in a batch reactor to assess the effect of different heating rates on the product yield and its composition. The effect of residence time during fast pyrolysis (Isothermal) in Pyro-GC was also investigated. Initially, TG analysis was performed to investigate the degradation temperature range at different heating rates of 5, 10, 20 and 40 °C/min. Two different heating rates of 10 and 20 °C/min were selected for examining the effect on products such as oil and gases (H2, CO, CO2 and C1 -C6 hydrocarbons) during slow pyrolysis. The oil obtained at higher heating rate had higher density (0.743 kg/m 3 ) while the amount of residue decreased with the increase in heating rate. Also, the effect of residence time during fast pyrolysis was investigated using Pyro-GC at 500 °C for the product formation. It was observed that an optimum residence time of 10sec was favourable for the higher production of lower hydrocarbons (C1 -C3 ) and less production of heavier hydrocarbons (C6 ). This work represents the combined analysis of fast and slow pyrolysis and their impact on the product yield. Also, the effect of heating rate on non-isothermal condition and the effect of the residence time of volatiles in isothermal condition was analysed and reported. Highlights: Effect of fast and slow pyrolysis on product yield and its composition. Pyrolysis of post consumer plastic waste for valuable product recovery. Degradation of mixed and individual plastic waste via TGA. Effect of heating rate in non-isothermal conditions. Continuous gas generation analysis during non-isothermal pyrolysis.